Characterization of Flavin-Containing Opine Dehydrogenase from Bacteria - Watanabe, Seiya; Sueda, Rui; Fukumori, Fumiyasu; Watanabe, Yasuo (PLOS ONE, 2015)
Opines, in particular nopaline and octopine, are specific compounds found in crown gall tumor tissues induced by infections with Agrobacterium species, and are synthesized by well-studied NAD(P)H-dependent dehydrogenases (synthases), which catalyze the reductive condensation of α-ketoglutarate or pyruvate with L-arginine. The corresponding genes are transferred into plant cells via a tumor-inducing (Ti) plasmid. In addition to the reverse oxidative reaction(s), the genes noxB-noxA and ooxB-ooxA are considered to be involved in opine catabolism as (membrane-associated) oxidases; however, their properties have not yet been elucidated in detail due to the difficulties associated with purification (and preservation). We herein successfully expressed Nox/Oox-like genes from Pseudomonas putida in P. putida cells. The purified protein consisted of different α-, β-, and γ-subunits encoded by the OdhA, OdhB, and OdhC genes, which were arranged in tandem on the chromosome (OdhB-C-A), and exhibited dehydrogenase (but not oxidase) activity toward nopaline in the presence of artificial electron acceptors such as 2,6-dichloroindophenol. The enzyme contained FAD, FMN, and [2Fe-2S]-iron sulfur as prosthetic groups. On the other hand, the gene cluster from Bradyrhizobium japonicum consisted of OdhB1-C-A-B2, from which two proteins, OdhAB1C and OdhAB2C, appeared through the assembly of each β-subunit together with common α- and γ-subunits. A poor phylogenetic relationship was detected between OdhB1 and OdhB2 in spite of them both functioning as octopine dehydrogenases, which provided clear evidence for the acquisition of novel functions by “subunit-exchange”. To the best of our knowledge, this is the first study to have examined flavin-containing opine dehydrogenase.